SOSIALISASI DAN EDUKASI DAGUSIBU OBAT DENGAN BENAR PADA MASYARAKAT KELURAHAN TATURA UTARA, PALU SELATAN - Dewi, Niluh Puspita; Wirawan, Wayan; Rakanita, Yasinta; Polontalo, Nani Astria; Insani, Fadillah (Jurnal Abdi Insani, 2025)
Various health problems, particularly those related to drugs, persist in the community. This can be caused by a lack of public understanding of the proper use and handling of drugs. The DAGUSIBU program is one method for proper drug management. The goal of DAGUSIBU outreach is to increase public understanding of drugs and how to manage and monitor their proper use. The methods used include public education through counseling and practical training. The effectiveness of the outreach was tested using pre- and post-tests, as well as a community satisfaction questionnaire. The results showed an increase in public knowledge and understanding after the DAGUSIBU outreach and education activities. Overall, the average increase in knowledge and understanding of DAGUSIBU among participants was 84%. This can help the government provide better health services. By improving participants' understanding of proper drug management, this outreach is expected to enable them to utilize the knowledge they gain within their families and communities.